Algunos aspectos relacionados con el control integrado de plagas en frijol (Phaseolus vulgaris L.) - Melendez E, A (International Center for Tropical Agriculture, 1974)
Integrated pest control uses a combination of methods to maintain pest populations at an economically tolerable level. After listing the principal bean pests in the zone of Palmira, Valle del Cauca (Colombia) and the type of damage they cause, cultural, chemical and biological methods are discussed, especially in relation to Empoasca kraemeri, the main pest. (CIAT)